Review on Multifactorial Coupling Effects and the Time-Dependent Behavior of Lateral Pressure on Concrete Formworks - Kekuo Yuan; Min Zhang; Yichu Lu; Hongdan Yu (Buildings)
This critical review synthesizes evidence on the multifactorial coupling mechanisms and time-dependent evolution of lateral pressure in concrete formworks, addressing significant limitations in current design standards (GB50666, CIRIA 108, ACI 347). Through a structured analysis of 60+ experimental and theoretical studies, we establish that lateral pressure is governed by nonlinear interactions between concrete rheology, casting dynamics, thermal conditions, and formwork geometry. The key findings reveal that (1) casting rate increments >5 m/h amplify peak pressure by 15–27%, while SCC thixotropy (Athix > 0.5) reduces it by 15–27% at <5 m/h; (2) secondary vibration induces 52–61% pressure surges through liquefaction; and (3) sections with a width >2 m exhibit 40% faster pressure decay due to arching effects. (4) Temporal evolution follows three distinct phases—rapid rise (0–2 h), slow decay (2–10 h), and sharp decline (>10 h)—with the temperature critically modulating transition kinetics. Crucially, the existing codes inadequately model temperature dependencies, SCC/HPC rheology, and high-speed casting (>10 m/h). This work proposes a parameter-specific framework integrating rheological thresholds (Athix, Rstr), casting protocols, and real-time monitoring to enhance standard accuracy, enabling an optimized formwork design and risk mitigation in complex scenarios, such as water conveyance construction and slipforming.